Lateral Leaflet Suppression 1 (LLS1), encoding the MtYUCCA1 protein, regulates lateral leaflet development in Medicago truncatula. Issue 2 (23rd April 2020) - Zhao, Baolin; He, Liangliang; Jiang, Chuan; Liu, Ye; He, Hua; Bai, Quanzi; Zhou, Shaoli; Zheng, Xiaoling; Wen, Jiangqi; Mysore, Kirankumar S.; Tadege, Million; Liu, Yu; et al.
Summary: In species with compound leaves, the positions of leaflet primordium initiation are associated with local peaks of auxin accumulation. However, the role of auxin during the late developmental stages and outgrowth of compound leaves remains largely unknown. Using genome resequencing approaches, we identified insertion sites at four alleles of the LATERAL LEAFLET SUPPRESSION1 ( LLS1 ) gene, encoding the auxin biosynthetic enzyme YUCCA1 in Medicago truncatula . Linkage analysis and complementation tests showed that the lls1 mutant phenotypes were caused by the Tnt1 insertions that disrupted the LLS1 gene. The transcripts of LLS1 can be detected in primordia at early stages of leaf initiation and later in the basal regions of leaflets, and finally in vein tissues at late leaf developmental stages. Vein numbers and auxin content are reduced in the lls1‐1 mutant. Analysis of the lls1 sgl1 and lls1 palm1 double mutants revealed that SGL1 is epistatic to LLS1, and LLS1 works with PALM1 in an independent pathway to regulate the growth of lateral leaflets. Our work demonstrates that the YUCCA1/YUCCA4 subgroup plays very important roles in the outgrowth of lateral leaflets during compound leaf development of M. truncatula, in addition to leaf venation.